2010
DOI: 10.1002/asna.201011459
|View full text |Cite
|
Sign up to set email alerts
|

Is macroturbulent broadening in OB Supergiants related to pulsations?

Abstract: The spectrum of O and B Supergiants is known to be affected by an important extra line-broadening (usually called macroturbulence) that adds to stellar rotation. Recent analysis of high resolution spectra has shown that the interpretation of this line-broadening as a consequence of large-scale turbulent motions would imply highly super-sonic velocity fields, making this scenario quite improbable. Stellar oscillations have been proposed as a likely alternative explanation. We present first encouraging results o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Aerts et al (2009) notably suggested that non-radial pulsations could trigger large-scale motions (hence macroturbulence), but this needs to be confirmed by a study covering a wider parameter space. A study by Simón-Díaz et al (2010) also showed that the amplitude of macroturbulence was correlated to the amplitude of line profile variability in a sample of OB supergiants. In practice, we introduce macroturbulence by convolving our rotationally broadened synthetic spectra with a Gaussian profile, thus mimicking isotropic turbulence.…”
Section: Modellingmentioning
confidence: 89%
“…Aerts et al (2009) notably suggested that non-radial pulsations could trigger large-scale motions (hence macroturbulence), but this needs to be confirmed by a study covering a wider parameter space. A study by Simón-Díaz et al (2010) also showed that the amplitude of macroturbulence was correlated to the amplitude of line profile variability in a sample of OB supergiants. In practice, we introduce macroturbulence by convolving our rotationally broadened synthetic spectra with a Gaussian profile, thus mimicking isotropic turbulence.…”
Section: Modellingmentioning
confidence: 89%
“…Aerts et al (2009) recently suggested that non-radial pulsations could trigger large-scale motions (hence macroturbulence), but this needs to be confirmed by a study covering a wider parameter space. A recent study by Simón-Díaz et al (2010) showed that the amplitude of macroturbulence was correlated to the amplitude of line profile variability in a sample of OB supergiants.…”
Section: Modellingmentioning
confidence: 99%
“…Though the physical origin of this broadening still remains to be proven, there are some strong indications that it is associated with (high order, non-radial) stellar pulsations (Aerts et al 2009;Simón-Díaz et al 2010). To account for this effect, we used a radial-tangential description of v mac to fit the profile shapes of nitrogen (and partly helium) lines, using our first estimates on the stellar and wind parameters (see above) and the new v sin i values.…”
Section: Determination Of Stellar and Wind Parametersmentioning
confidence: 99%